2008
DOI: 10.1007/s11469-008-9158-0
|View full text |Cite
|
Sign up to set email alerts
|

Dysthymia among Substance Abusers: An Exploratory Study of Individual and Mental Health Factors

Abstract: The purpose of this study was to examine the individual characteristics and mental health factors of dysthymic and nondysthymic substance abusers. Out of a total of 1,209 medical records reviewed to select cases of dysthymic and nondysthymic substance abusers attending a community drug treatment program, 183 medical records were selected, 48% of which were dysthymic substance abusers. Bivariate analyses indicated that dysthymic substance abusers were more likely to be male, older individuals, reported high lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
1

Year Published

2009
2009
2016
2016

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 32 publications
1
5
1
Order By: Relevance
“…This is not consistent with existing evidence suggesting that the comorbidity of mood disorder and substance abuse is associated to continued drug use and drug relapse (Stein, Solomon, Herman, Anderson & Miller, 2003;Strowig, 2000), whereby dysthymic respondents tended to report higher number of previous substance abuse treatments compared to non-dysthymics (Diaz et al, 2008). However, it is important to note that most of the participants in this study were employed professionals, able to perform their responsibilities at an adequate level interacting with colleagues and the public, and thus perhaps functioning at a higher level that the respondents in these earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…This is not consistent with existing evidence suggesting that the comorbidity of mood disorder and substance abuse is associated to continued drug use and drug relapse (Stein, Solomon, Herman, Anderson & Miller, 2003;Strowig, 2000), whereby dysthymic respondents tended to report higher number of previous substance abuse treatments compared to non-dysthymics (Diaz et al, 2008). However, it is important to note that most of the participants in this study were employed professionals, able to perform their responsibilities at an adequate level interacting with colleagues and the public, and thus perhaps functioning at a higher level that the respondents in these earlier studies.…”
Section: Discussioncontrasting
confidence: 99%
“…Results indicated that over half of the sample (n ¼ 39) reported clinically significant MCMI-III scores on the dysthymia scale. This is consistent with previous research indicating a high prevalence of dysthymia among residential substance abusers (Diaz et al, 2008). In addition, findings indicated elevated comorbidity between dysthymia and multiple Axes I and II disorders.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations